Optimisation of the finish hard turning process for hardened 52100 steel with PCBN tools. (13th September 2007) - Zhang, JingYing; Liang, Steven Y.; Yen, David
This study develops a methodology for the planning of optimal tool geometry and cutting conditions to achieve specific performance goals, a satisfactory surface finish, and other practical constraints, while using the example of finish turning of hardened AISI 52100 bearing steel with Low CBN tools. A hierarchical structure modelling scheme for predicting white layer thickness and residual stress profiles is pursued to integrate the existing experimental, numerical and analytical knowledge into the process planning in an effective manner. Other hard turning process models, including temperature, force, surface roughness and tool wear, are also presented. Some of those models are non-explicit and are not analytically differentiable from the design variables, which renders traditional nonlinear optimisation techniques difficult to apply. An evolutionary optimisation scheme, a Mixed Integer Evolutionary Algorithm (MIEA), has been applied for this process optimisation problem. The optimal design outcomes derived from the methodology in this study were compared to other experimental and analytical work results for validation.